A Conceptual Analysis of Performance Attributes’ Influence on NBA Attendance: Why Do Consumers Choose to Attend Games? - Mark Andrew Davis; John Miller (Journal of Applied Sports Management, 2019)
Fans want to capitalize on their choices when deciding whether to attend NBA games. The purpose of this study is to provide a conceptual analysis regarding how overall team performances as well as offensive and defensive factors may relate to consumers choosing to attend NBA games during the 2007-2008 to 2016-2017 sea-sons. Analyzing the results through the lens of the theory of choice, the results revealed significant relationships existed primarily between attendance at NBA games and offensive capabilities of the teams. As a practical matter, consumers choose to attend games that are most likely to be offensively oriented. Subscribe to JASM
Keywords: NBA attendance; hedonic consumption